Characterization of alkyl phenols in cashew (Anacardium occidentale) products and assay of their antioxidant capacity - Trevisan, Maria T.S.; Pfundstein, B.; Haubner, R.; Würtele, G.; Spiegelhalder, Bertold; Bartsch, Helmut; Owen, Robert (Food and chemical toxicology, 2006)
In this study the content of anacardic acids, cardanols and cardols in cashew apple, nut (raw and roasted) and cashew nut shell liquid (CNSL) were analysed. The higher amounts (353.6g/kg) of the major alkyl phenols, anacardic acids were detected in CNSL followed by cashew fibre 6.1g/kg) while the lowest (0.65g/kg) amounts were detected in roasted cashew nut. Cashew apple and fibre contained anacardic acids exclusively, whereas CNSL also contained an abundance of cardanols and cardols. Cashew nut (raw and roasted) also contained low amounts of hydroxy alkyl phenols. Cashew nut shell liquid was used for a basic fractionation of the alkyl phenol classes and the individual anacardic acids, major cardanols and cardols were purified to homogeneity from these fractions by semi-preparative HPLC and definitively identified by nano-ESI-MS-MS, GC-MS and NMR analyses. The hexane extracts (10mg/ml) of all cashew products tested plus CNSL, displayed significant antioxidant capacity. Cashew nut shell liquid was the more efficient (inhibition=100%) followed by the hexane extract of cashew fibre (94%) and apple (53%). The antioxidant capacity correlated significantly (P<0.05) with the concentration of alkyl phenols in the extracts. A mixture of anacardic acids (10.0mg/ml) showed the higher antioxidant capacity (IC50=0.60mM) compared to cardols and cardanols (IC50>4.0mM). The data shows that of these substances, anacardic-1 was by far the more potent antioxidant (IC50=0.27mM) compared to cardol-1 (IC50=1.71mM) and cardanol-1 (IC50>4.0mM). The antioxidant capacity of anacardic acid-1 is more related to inhibition of superoxide generation (IC50=0.04mM) and xanthine oxidase (IC50=0.30mM) than to scavenging of hydroxyl radicals. At present a substantial amount of cashew fibre is mostly used in formulations of animal or poultry feeds. The data presented in this study, indicates that this waste product along with CNSL, both of which contain high contents of anacardic acids, could be better utilized in functional food formulations and may represent a cheap source of cancer chemopreventive agents.